Policy Implementation and Learning Outcomes: An Analytical Study of Education Reform Frameworks - Wellty Mely Betesda Br Sinaga; Renova Manullang; Melia Putri Utami (Institute of Information Technology and Social Science (IITSS), 2021)
The main aim of this research is to pinpoint the problems that need to be addressed through educational policy and to gain comprehensive knowledge about the underlying causes of these problems. This research approach is a library research method or literature study. Relevant literature, which includes books, journals and scientific papers on the selected issue, is used as a source of research data. The findings of this study indicate that, from a technical perspective, education policy development is the most important aspect of the ongoing policy analysis process. Therefore, the phrase â€œthe circle of education policy that keeps turningâ€ is not surprising when discussing the process of developing education policy. It is important for education policies to be carefully designed to minimize disruption. new educational issues that go beyond existing issues that need to be addressed or resolved in terms of complexity, breadth, and depth. Identifying the correct problem is undoubtedly necessary for successful problem solving. Different conceptualizations of an educational problem condition are produced and tested through the formation of educational policy challenge.